Acute Cholecystitis Complicated with Portal Vein Thrombosis: A Case Report and Literature Review - Muneer, Mohammed (Am J Case Rep, 2015)
Patient: Male, 31 Final Diagnosis: Acute cholecystitis complicated with portal vein thrombosis Symptoms: Abdominal discomfort • fever • vomiting Medication: — Clinical Procedure: Abdominal ultrasound and MRI Specialty: Gastroenterology and Hepatology OBJECTIVE: Rare co-existance of disease or pathology BACKGROUND: Portal vein thrombosis (PVT) is an infrequent clinical condition usually associated with multiple etiological factors and diseases. In some cases, PVT remains undiagnosed and is incidentally detected during routine examination for a known etiology. CASE REPORT: Here, we present a rare case of portal vein thrombosis associated with acute cholecystitis in a 31-year-old man. CONCLUSIONS: Conservative treatment may be a feasible and safe approach for the management of PVT with acute cholecystitis, if treated at an early stage. Moreover, initial diagnosis based on radiological evaluation is possible only if the surgeons are familiar with this unusual condition. Therefore, a high index of suspicion is required for early diagnosis and management of patients with acute cholecystitis-associated PVT.